Pengaruh Employer Branding, Reputasi Perusahaan, dan Recruitment Terhadap Minat Melamar Kerja di Kawasan Industri Cikarang - Prasetio, Chandra Dimas; Setyaningrum, Retno Purwani (Jurnal Doktor Manajemen (JDM), 2024)
The development of technology in Indonesia is quite rapid, which means that competition between companies will also be increasingly competitive. The phenomenon in this study is how companies located in the Cikarang industrial area, which is one of the largest industrial areas in Indonesia, can maintain their existence in this era which technology rapidly developing through several aspects, namely Employer Branding, Company Reputation, and Recruitment. The potential that has been achieved will make the company's reputation increase. This type of research is quantitative research using descriptive methods. The processed data is primary data obtained from the results of distributing questionnaires. Obtained respondents as many as 80 people. The data processing technique uses Smart PLS (Partial Least Square). The results of this study indicate that employer branding has no effect on interest in applying for work. Company reputation also has no effect on interest in applying for work and Recruitment has a positive effect on interest in applying for work.